Hereditary Contribution Towards Development of Type 2 Diabetes Mellitus among Indian Population - Nilupher Feroz; Meenal Dhall; Satwanti Kapoor (Diabetes Research, 2019)
Diabetes Mellitus Type II is becoming a major disorder. This study describes the inheritance of type 2 diabetes mellitus in families with diabetes. Methods The study was conducted in Manipur in two districts i.e., Imphal-east and Thoubal among Muslim families. These families were considered for the present study in which one or more family members had diabetes and were involved as active participants. Results On tracing the genealogies of each family, a higher percentage of the participants with diabetes inherited the disease from their fathers. Conclusions This finding would be helpful in future research by implementing among different communities.